2012
DOI: 10.1007/978-3-642-33263-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Paper Interfaces for Learning Geometry

Abstract: Abstract. Paper interfaces offer tremendous possibilities for geometry education in primary schools. Existing computer interfaces designed to learn geometry do not consider the integration of conventional school tools, which form the part of the curriculum. Moreover, most of computer tools are designed specifically for individual learning, some propose group activities, but most disregard classroom-level learning, thus impeding their adoption. We present an augmented reality based tabletop system with interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We developed several pedagogical scenarios based on paper interfaces, which we deployed in three primary schools and with more than 20 classes (Bonnard, Verma, Kaplan & Dillenbourg, 2012). The activities involve various geometry topics: classifying quadrilaterals, measuring and describing angles, finding the formulas for areas, etc.…”
mentioning
confidence: 99%
“…We developed several pedagogical scenarios based on paper interfaces, which we deployed in three primary schools and with more than 20 classes (Bonnard, Verma, Kaplan & Dillenbourg, 2012). The activities involve various geometry topics: classifying quadrilaterals, measuring and describing angles, finding the formulas for areas, etc.…”
mentioning
confidence: 99%
“…al. observed that paper based interfaces can be easily adopted into traditional classroom practices [3] [4]. They designed a tabletop system to facilitate geometry learning, seamlessly integrating it with conventional geometry tools.…”
Section: Related Workmentioning
confidence: 99%
“…Interactive tabletops have been applied successfully in geometry learning in primary schools [1]. Using the same technology, we developed a system for learning about fractions, using paper-based manipulatives.…”
Section: A System For Augmented-paper Fraction Learn-ingmentioning
confidence: 99%
“…We implemented a central point of control in a tabletop collaborative learning application (based on the TinkerLamp system, see [1]), to synchronize group work and afford opportunities for reflection, thus avoiding unequal participation. Considering group dynamics, we investigate how primary school students working in small groups use this single central control to complete their group tasks, by examining its position and rotation.…”
Section: Introductionmentioning
confidence: 99%